PENGARUH PEMILIHAN PRODUK SUSU KEMASAN KARTON TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN - eka destriyanto ayuningtyas (Universitas Muhammadiyah Ponorogo, 2016)
The core of the problem which was discussed in this reaserch was the big influence cover of a product toward a decision in buying milk product carton type. The reaserch used explanatory reaserch by quantitive approach. The technique of collecting data used questionnaire and interview to the 100 mothers as the respondents.Technique analyse data used factor analysis, Regresi analysis and regresi partial analysis. Based on the result which could be taken from the research that the cover has influenced and significant enough to a decision bought by consumers, so it was needed by producers in producing products which would be sold that can attract the consumers to buy it